Electrochemical formation of Cr(III)-based films on Au electrodes. (10th February 2019) - Smulders, Vera; Simic, Nina; Gomes, Adriano S.O.; Mei, Bastian; Mul, Guido
Abstract: In electrochemical production of sodium chlorate from brine solutions, an intriguing function of sodium (di)chromate is to inhibit cathodic reduction of oxychlorides, while maintaining effective reduction of water to form hydrogen. Using an electrochemical Quartz Crystal Microbalance (eQCM) and a Rotating Ring Disk Electrode (RRDE; Au disk, Pt ring), we analyzed the deposition of reduced Cr-species formed from reduction of Cr VI O4 2− on Au electrodes. Generally, the current induced by reduction of Cr VI O4 2− is significantly larger than the accumulated amount of weight deposited on the Au electrode. Deconvolution of the reductive peak reveals two processes that can be differentiated by varying rotation speed. We therefore propose soluble Cr V O4 3− is formed by reduction of Cr VI O4 2−, followed by consecutive reduction of Cr V O4 3− to primarily soluble Cr III (OH)4 - . Simultaneously, reduction of Cr V O4 3− also leads to the formation of a monolayer of Cr III (hydr)oxide. This monolayer significantly inhibits the further reduction of Cr VI O4 2−, but allows the film to reach a maximum thickness of approximately 1.85 nm by reduction of surface adsorbed Cr V O4 3− and/or de-hydroxylation of Cr III (OH)4 - . The observation that limitation of film growth is due to film-induced inhibition of reduction of Cr VI O4 2−, and significant solubility of Cr III (OH)3 in the form of Cr III (OH)4 -, will aid in the search of a non-toxic chrome-free alternative for inhibition of cathodic reduction of oxychlorides and selective hydrogen evolution in the chlorate process. Graphical abstract: Redox chemistry leading to deposition of Cr III Ox from Na2 Cr2 O7 on a Au electrode. Image 1